Pengembangan Lembar Aktivitas Peserta Didik (LAPD) Berbasis Problem Based Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Peserta Didik Pada Materi Elektrolit dan Nonelektrolit Fase F - Adelia Putri Rahmadania; Rusmini Rusmini (PendIPA Journal of Science Education, 2026)
This research was conducted to design a Problem Based Learning (PBL)-based Student Activity Worksheet (LAPD) for the topic of electrolyte and non-electrolyte solutions, while evaluating its validity, practicality, and effectiveness in enhancing students' critical thinking abilities. The approach employed was Research and Development (R&D) using the 4-D model, encompassing the phases of definition, design, development, and dissemination. Limited product trials were carried out with 32 students at SMA Negeri 1 Gedangan utilizing a One Group Pretest-Posttest design. Data collection tools included validation sheets, student response questionnaires, activity observation forms, and critical thinking skills assessments. Research findings revealed that the developed LAPD achieved a highly valid rating according to expert evaluations. Its practicality was demonstrated by a 98.52% student response rate (categorized as excellent) and 100% relevant student engagement during learning sessions. Meanwhile, the LAPD's effectiveness was evident in the observed improvement in students' critical thinking skills, as measured by N-gain scores falling in the moderate category. These results were further supported by paired sample t-test analysis, yielding a significance value <0.05, indicating a substantial difference between pretest and posttest scores. Based on these outcomes, the PBL-based LAPD is deemed valid, practical, and effective for advancing students' critical thinking skills on electrolyte and non-electrolyte solution topics.